Economic Comparison of Hand-Sutured and Coupler-Assisted Microvascular Anastomoses - Head, Linden K.; McKay, Douglas R. (Journal of Reconstructive Microsurgery, 2018)
Background Compared with hand-sewn anastomoses, microvascular anastomotic coupling devices (MACDs) provide equivalent flap survival and reduced operative time. To date, an economic analysis of MACDs has not been reported. The objective of this study was to evaluate the economics of a venous anastomosis performed using a coupling device compared with a hand-sewn anastomosis.Methods Economics were modeled for a single free tissue transfer (FTT) requiring one venous anastomosis performed with either hand-sewn sutures or with a coupler-assisted anastomosis using the GEM COUPLER. Fixed and variable costs incurred with each anastomotic technique were identified with an activity-based cost analysis. Price lists were retrieved from suppliers to quantify disposable costs and capital expenditures. Two literature reviews were executed to identify microsurgical operating room (OR) costs and operating time reductions with coupler-assisted anastomoses.Results For each venous anastomosis, the use of the anastomotic coupler increased disposable costs by $284.40 compared with a hand-sutured anastomosis. Total fixed and variable OR costs were $30.82 per minute. Operating time was reduced by a mean of 16.9 minutes with a coupler-assisted anastomosis, decreasing OR costs by $519.29. Total savings of $234.89 were generated for each coupler-assisted anastomosis, recuperating the device's capital expenditure after 13 uses.Conclusion Compared with a hand-sewn venous anastomosis, an MACD produces savings with each case and quickly recoups the device's capital expenditure. Despite its limitations and simplicity, this study provides a practical economic analysis that can help inform purchasing decisions, particularly for smaller volume centers where the economic rationale may be less clear.
Keywords: microvascular anastomotic coupling device (MACD); microsurgery; economics